Urinary Extracellular Vesicles as a Source of NGAL for Diabetic Kidney Disease Evaluation in Children and Adolescents With Type 1 Diabetes Mellitus - Ugarte, Francisca; Santapau, Daniela; Gallardo, Vivian; Garfias, Carolina; Yizmeyián, Anahí; Villanueva, Soledad; Sepúlveda, Carolina; Rocco, Jocelyn; Pasten, Consuelo; Urquidi, Cinthya; Cavada, Gabriel; San Martin, Pamela; et al. (Frontiers in Endocrinology, 2022)
Background Tubular damage has a role in Diabetic Kidney Disease (DKD). We evaluated the early tubulointerstitial damage biomarkers in type-1 Diabetes Mellitus (T1DM) pediatric participants and studied the correlation with classical DKD parameters. Methods Thirty-four T1DM and fifteen healthy participants were enrolled. Clinical and biochemical parameters [Glomerular filtration Rate (GFR), microalbuminuria (MAU), albumin/creatinine ratio (ACR), and glycated hemoglobin A1c (HbA1c)] were evaluated. Neutrophil gelatinase-associated lipocalin (NGAL), Hypoxia-inducible Factor-1α (HIF-1α), and Nuclear Factor of Activated T-cells-5 (NFAT5) levels were studied in the supernatant (S) and the exosome-like extracellular vesicles (E) fraction from urine samples. Results In the T1DM, 12% had MAU >20 mg/L, 6% ACR >30 mg/g, and 88% had eGFR >140 ml/min/1.72 m2. NGAL in the S (NGAL-S) or E (NGAL-E) fraction was not detectable in the control. The NGAL-E was more frequent (p = 0.040) and higher (p = 0.002) than NGAL-S in T1DM. The T1DM participants with positive NGAL had higher age (p = 0.03), T1DM evolution (p = 0.03), and serum creatinine (p = 0.003) than negative NGAL. The NGAL-E correlated positively with tanner stage (p = 0.0036), the median levels of HbA1c before enrollment (p = 0.045) and was independent of ACR, MAU, and HbA1c at the enrollment. NFAT5 and HIF-1α levels were not detectable in T1DM or control. Conclusion Urinary exosome-like extracellular vesicles could be a new source of early detection of tubular injury biomarkers of DKD in T1DM patients.